1989
DOI: 10.1523/jneurosci.09-09-03287.1989
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a cell-surface protein involved in PC12 cell- substratum adhesion and neurite outgrowth on laminin and collagen

Abstract: On substrata coated with laminin or native collagen (Types I/III), PC12 cells employ an active adhesion mechanism (i.e., one inhibited at low temperature, by azide or in the absence of divalent cations) to attach and extend neurites; on substrata coated with wheat germ agglutinin (WGA) or polylysine, by contrast, PC12 cells attach via a passive mechanism and fail to extend neurites (Turner et al., 1987). This paper reports the isolation of 2 monoclonal antibodies (3A3 and 1B1) that promote retraction of neurit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0
2

Year Published

1990
1990
1999
1999

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 58 publications
3
119
0
2
Order By: Relevance
“…In fact. Kramer and Marks (1989) noted that functionally inhibitory antibodies would be necessary to confirm their results since affinity chromatography of integrins in detergent-containing solutions may not always reflect the function of a receptor in vivo (Wayner & Carter, 1987;Hynes et al, 1989). We conclude that the rat and human α 1 β 1 integrins are receptors that bind directly to sites in laminin and collagen.…”
Section: Resultsmentioning
confidence: 99%
“…In fact. Kramer and Marks (1989) noted that functionally inhibitory antibodies would be necessary to confirm their results since affinity chromatography of integrins in detergent-containing solutions may not always reflect the function of a receptor in vivo (Wayner & Carter, 1987;Hynes et al, 1989). We conclude that the rat and human α 1 β 1 integrins are receptors that bind directly to sites in laminin and collagen.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that integrins function in cell matrix adhesion in PC12 cells (Tomaselli et al, 1988(Tomaselli et al, , 1990Turner et al, 1989). The cvl@l is the dominant integrin-mediating neurite outgrowth, and the a3P 1 heterodimer is a relatively weak receptor (Tomaselli et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…antibodies alone are ineffective, whereas antibodies to al partially inhibit neurite extension (Turner et al, 1989;Tomaselli et al, 1990).…”
Section: Discussionmentioning
confidence: 99%